The measurement properties of the Lean-and-Release test in people with incomplete spinal cord injury or disease. (4th May 2022) - Unger, Janelle; Oates, Alison R.; Lanovaz, Joel; Chan, Katherine; Lee, Jae W.; Theventhiran, Pirashanth; Masani, Kei; Musselman, Kristin E.
Abstract : Objective: To evaluate test-retest reliability, agreement, and convergent validity of the Lean-and-Release test for the assessment of reactive stepping among individuals with incomplete spinal cord injury or disease (iSCI/D). Design: Multi-center cross-sectional multiple test design. Setting: SCI/D rehabilitation hospital and biomechanics laboratory. Participants: Individuals with motor incomplete SCI/D (iSCI/D). Interventions: None. Outcome Measures: Twenty-six participants attended two sessions to complete the Lean-and-Release test and a battery of clinical tests. Behavioral ( i.e. one-step, multi-step, loss of balance) and temporal ( i.e. timing of foot off, foot contact, swing of reactive step) parameters were measured. Test-retest reliability was determined with intraclass correlation coefficients, and agreement was evaluated with Bland–Altman plots. Convergent validity was assessed through correlations with clinical tests. Results: The behavioral responses were reliable for the Lean-and-Release test (ICC = 0.76), but foot contact was the only reliable temporal parameter using data from a single site (ICC = 0.79). All variables showed agreement according to the Bland–Altman plots. The behavioral responses correlated with scores of lower extremity strength (0.54, P<0.01) and balance confidence (0.55, P < 0.01). Swing time of reactive stepping correlated with step time (0.73, P < 0.01) and cadence (−0.73 P < 0.01) of over ground walking. Conclusions: The behavioral response of the Lean-and-Release test is a reliable and valid measure for people with iSCI/D. Our findings support the use of the behavioral responses to evaluate reactive stepping for research and clinical purposes. Trial registration: ClinicalTrials.gov identifier: NCT02960178 .